1996
DOI: 10.1016/0014-5793(95)01446-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the catalytic activity of human transaldolase by antibodies and site‐directed mutagenesis

Abstract: Transaldolase is a key enzyme of the pentose phosphate pathway. While antibody (Ab) 169, directed against the N-terminal 139 residues of human transaldolase (TAL-H), had no effect on enzyme activity, Ab 12484 raised against full length and functional recombinant TAL-H inhibited catalytic activity. This tentatively mapped the catalytic site to the C-terminal 140-336 amino acid portion of TAL-H. Dihydroxyacetone transfer reactions catalyzed by transaldolase depend on Schiff base formation by a iysine residue. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Catalytic activity of rTAL-H was also inhibited in the presence of purified Igs from MS patients ALV and LAK. These data demonstrated that high affinity autoantibodies from patients with MS recognized not only the immunoblotted fulllength TAL-H protein and its NH 2 -terminal fragment (16) but functionally relevant COOH-terminal epitopes as well (38). The presence of autoantibodies to multiple TAL-H epitopes and the enzyme inhibitory capacity of a subset of autoantibodies suggests that the intact TAL-H protein has become the source of antigenic drive in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Catalytic activity of rTAL-H was also inhibited in the presence of purified Igs from MS patients ALV and LAK. These data demonstrated that high affinity autoantibodies from patients with MS recognized not only the immunoblotted fulllength TAL-H protein and its NH 2 -terminal fragment (16) but functionally relevant COOH-terminal epitopes as well (38). The presence of autoantibodies to multiple TAL-H epitopes and the enzyme inhibitory capacity of a subset of autoantibodies suggests that the intact TAL-H protein has become the source of antigenic drive in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Patients with MS have TAL Abs in their blood and cerebrospinal fluid (21)(22)(23)(24)(25)(26)(27)(28)(29). TAL autoantibodies recognize immunoblotted and three-dimensional epitopes and inhibit enzymatic activity of TAL (36). By constrast, TAL Abs were absent in normal individuals and patients with other autoimmune and neurological diseases (21) and, under identical conditions, no MBP Abs were found in serum and cerebrospinal fluid of MS patients (29).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…7A, which is published as supporting information on the PNAS web site). This manipulation deleted amino acid residues 138-153, including lysine 142, which is essential for catalytic activity of TAL (11). The 129SvJ-derived TC1 ES cells heterozygous for the disrupted allele were microinjected into C57BL͞6 blastocysts to generate chimeras.…”
Section: Inactivation Of the Mouse Tal (Tal-m) Gene Locus By Homologousmentioning
confidence: 99%